Research on Fatigue Life and Node Displacement Modification Method of Helical Gears - Li Yufeng; Li Dongyang; Wu Luji; Ge Shixiang; Yang Yongfei; Chang Hao (Jixie chuandong)
In response to the difficulties in analyzing the fatigue life of gear transmission systems and the limitations of shape modification, the Adams dynamic simulation is used to obtain the time-domain contact force curve as the simulation analysis load spectrum. Combined with the finite element static solution process and the S-N curve of gear materials, the fatigue life of helical gear pairs is analyzed in nCode. On the basis of the strain analysis guidance, a node displacement modification method is proposed, which integrates the deformation of equidistant section nodes through K-Means clustering. The tooth profile correction curve is obtained by using the optimal symbolic node displacement class index basis function fitting method, which is highly consistent with the deformation generated by the load on the gear teeth. Compared with traditional linear modification, the fatigue life is increased by 16.98%. By providing feedback on the node deformation, the uneven load distribution during the gear meshing can effectively correct the involute tooth profile, balance the force distribution at the meshing interface, and extend the fatigue life.